2014
DOI: 10.1155/2014/169216
|View full text |Cite
|
Sign up to set email alerts
|

Serum Oxidative Stress Markers and Lipidomic Profile to Detect NASH Patients Responsive to an Antioxidant Treatment: A Pilot Study

Abstract: Liver steatosis can evolve to steatohepatitis (NASH) through a series of biochemical steps related to oxidative stress in hepatocytes. Antioxidants, such as silybin, have been proposed as a treatment of patients with nonalcoholic fatty liver disease (NAFLD) and NASH. In this study, we evaluated, in patients with histologically documented NASH, the oxidant/antioxidant status and lipid “fingerprint” in the serum of NASH patients, both in basal conditions and after 12 months of treatment with silybin-based food i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 27 publications
3
69
0
Order By: Relevance
“…For example, MALDI-IMS has been used to visualize the heterogeneous distribution of PC species in mouse brains [34], and effects of traumatic brain injury on the differential localization of PCs in rat brains [35]. Furthermore, MALDI-IMS detected alterations in phospholipid zonation in human livers with steatosis or nonalcoholic steatohepatitis (NASH) [36], and MALDI-TOF was used to measure serum lipidomic profiles in patients with NASH [37]. The present study examines the utility of MALDI-IMS for distinguishing glycerophospholipid profiles in experimental steatohepatitis produced in Long Evans rats by chronic ethanol, NNK or ethanol+NNK exposures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, MALDI-IMS has been used to visualize the heterogeneous distribution of PC species in mouse brains [34], and effects of traumatic brain injury on the differential localization of PCs in rat brains [35]. Furthermore, MALDI-IMS detected alterations in phospholipid zonation in human livers with steatosis or nonalcoholic steatohepatitis (NASH) [36], and MALDI-TOF was used to measure serum lipidomic profiles in patients with NASH [37]. The present study examines the utility of MALDI-IMS for distinguishing glycerophospholipid profiles in experimental steatohepatitis produced in Long Evans rats by chronic ethanol, NNK or ethanol+NNK exposures.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic response, mainly demonstrated by the improvement of liver damage, is reached in approximately 50% of the treated subjects. Moreover, we recently reported that this response was significantly correlated with the baseline serum oxidative stress, as well as with the variations of the serum oxidative and lipidomic profiles (16). In particular, we demonstrated that sera from patients with NASH induced lipid droplet accumulation in the cytoplasm of HepG2 cells, whereas a conditioning of the cells with sera of patients treated with silybin led to a reduction of intracellular fat accumulation.…”
mentioning
confidence: 64%
“…As reported in a previous study (16), we identified patients showing very low or very high levels of TBARS at baseline when compared to those of healthy controls. Thus, we divided patients (both P and R) into two groups on the basis of the trend of TBARS serum levels between baseline and after 12 months of treatment with P or R, in order to evaluate any potential differences of antioxidant response between these two groups.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The harmful effect of free radicals, intracellularly, is counteracted by the ability of cells to maintain the oxidative stress balance; oxidative stress occurs when the balance "prooxidant/antioxidant" is disturbed, and it generates the alteration of cellular structures, thus affecting lipid components, proteins, and nucleic acids [7].…”
Section: Introductionmentioning
confidence: 99%